Klasyfikacje budżetów - ujęcie praktyczne - Kes, Zdzisław (The Classifications of Budgets - the Practical Approach, 2006)
The article describes classifications of budgets found in the refered literature. The peper presents the attempt of evaluation of these classifications for business in respect of they usefulness and completeness. On this basis three additional classifications budgets were suggested.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 150-157